2005
DOI: 10.1124/dmd.105.006403
|View full text |Cite
|
Sign up to set email alerts
|

Digital Fluorescence Imaging of Organic Cation Transport in Freshly Isolated Rat Proximal Tubules

Abstract: ABSTRACT:The secretion of cationic drugs and endogenous metabolites is a major function of the kidney. This is accomplished by organic cation transport systems, mainly located in the proximal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Nevertheless, ASP þ uptake appeared to be highly effective, which is consistent with earlier in vitro reports. 10,14,15 However, we observed differences in the way intracellular ASP þ fluorescence decreased in proximal and distal tubules. In proximal tubules, intracellular ASP þ fluorescence decreased over time.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, ASP þ uptake appeared to be highly effective, which is consistent with earlier in vitro reports. 10,14,15 However, we observed differences in the way intracellular ASP þ fluorescence decreased in proximal and distal tubules. In proximal tubules, intracellular ASP þ fluorescence decreased over time.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, ASP þ was used for OC transport studies in other cell culture models [11][12][13] and in isolated proximal tubules. 14,15 Various experimental models have previously been applied for studies of OC transport including cellular substructures, 16,17 cell expression systems, 5 and cultured cells. 18,19 However, these experimental models possess particular limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the mechanisms underlying the renal secretion of organic ions is fundamental to gather new knowledge on the renal secretion of some molecules acting as uremic toxins and some drugs. To this aim, the ASP+ fluorescent molecule has been previously used [9][10][11][12][13]. Besides the usage of ASP+ in kidney research, ASP+ has been widely used, e.g., to identify dopamine transporter-positive neurons in vitro [20] and serotonin transporter-(SERT-) expressing cells and to evaluate the activity and regulation of SERT in vitro [21].…”
Section: Discussionmentioning
confidence: 99%
“…The organic cation 4-dimethylaminostyryl)-N-methylpyridinium (ASP+) was first defined as a probe for renal OC transport in experiments using the stopped flow technique in intact rat kidneys [9]. Since then, ASP+ has been proposed to be used for drug transport analysis [10] and widely used in various experimental settings [9][10][11][12][13]. Prior to the use in renal research, ASP+ was described as a fluorescent probe for living cells, which showed variable emission spectra depending on its interaction with different cellular structures [14] including mitochondria [15].…”
Section: Introductionmentioning
confidence: 99%